Smile regeneration by prosthodontic way- a case report - Sunil, D; Rajesh, P; Neha, D (Bangladesh Journal of Medical Science, 2012)
The realization of esthetic objectives and functional demands in the reconstruction of severely compromised dentition represents considerable clinical problems. This clinical report represents the prosthetic management of a severe dentofacial deformity with compromised periodontal status. Treatment objectives were based on Aesthetics enhancement, sociopsychological support of the patient, restoration of form function, phonetics and comfort. Following which extraction of upper incisors and alveoloplasty done. An immediate removable partial denture was fabricated, considering aesthetics, phonetics and comfort of the patient followed by replacement of incisors by metal- ceramic fixed partial denture done. Clinical relevance: prosthetic management of severlymalaligned natural maxillary anterior teeth by fixed partial denture, considering aesthetics and phonetics of the patient. Treatment objectives: Aesthetics enhancement, sociopsychological support of the patient, restoration of form function, phonetics and comfort. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9825 BJMS 2012; 11(1): 57-60